2010
DOI: 10.1177/1352458510372629
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome in women with multiple sclerosis: results from a prospective nationwide study in Finland

Abstract: The majority of individuals obtaining the diagnosis of multiple sclerosis are women of childbearing age. They are naturally concerned as to how multiple sclerosis affects the course of pregnancy and the developing foetus. The objective of this study was to prospectively evaluate the incidence of pregnancy complications and delivery risks, and to follow the natural course of multiple sclerosis during and after pregnancy in a cohort of Finnish patients with multiple sclerosis. Sixty-one patients with multiple sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
88
2
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 22 publications
4
88
2
7
Order By: Relevance
“…1 Recent studies have shown that pregnant MS patients have the same risk of pregnancy complications as the general population. 2 The influence of pregnancy on the course of disease in MS has also been studied over the years.According to the Pregnancy in Multiple Sclerosis (PRIMS) trial, the mean ± SD number of relapses was 0.7 ± 0.9 per woman per year in the year before pregnancy; it was 0.5 ± 1.3 during the first trimester of pregnancy, 0.6 ± 1.6 during the second trimester, and 0.2 ± 1.0 during the third trimester. It increased to 1.2 ± 2.0 during the first 3 months postpartum and then returned to the pre-pregnancy rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Recent studies have shown that pregnant MS patients have the same risk of pregnancy complications as the general population. 2 The influence of pregnancy on the course of disease in MS has also been studied over the years.According to the Pregnancy in Multiple Sclerosis (PRIMS) trial, the mean ± SD number of relapses was 0.7 ± 0.9 per woman per year in the year before pregnancy; it was 0.5 ± 1.3 during the first trimester of pregnancy, 0.6 ± 1.6 during the second trimester, and 0.2 ± 1.0 during the third trimester. It increased to 1.2 ± 2.0 during the first 3 months postpartum and then returned to the pre-pregnancy rate.…”
mentioning
confidence: 99%
“…1 Recent studies have shown that pregnant MS patients have the same risk of pregnancy complications as the general population. 2 The influence of pregnancy on the course of disease in MS has also been studied over the years.…”
mentioning
confidence: 99%
“…In some cases, clinical MS disease activity has also been described shortly before the delivery. 21 In conclusion, during the six-month postpartum period, 21 of 28 (75%) patients demonstrated MS disease activity either by a clinical MS relapse or by a T2 activity on the MRI scans.…”
Section: Mri During and After Pregnancymentioning
confidence: 99%
“…21 The mother's functional status should of course always be taken into account: a mother with significant functional disability will be more likely to encounter problems associated with fatigue and exhaustion during the second stage of delivery.…”
Section: Delivery Of Ms Mothersmentioning
confidence: 99%
“…Данные о фертильности женщин, страдающих РС, носят противоречивый характер: по данным K. Hellwig et al (2008), фертильность у женщин с РС не нарушена [7], в то время как по результатам исследования A. Jalkanen et al (2010) установлена более высокая потребность во вспомогательных ре-продуктивных технологиях (ВРТ) у пациенток с РС, по сравнению с населением в целом [8].…”
unclassified